3D Printing of NiZn ferrite/ABS Magnetic Composites for Electromagnetic Devices. Issue 1788 (2015) - Wang, Yunqi; Castles, Flynn; Grant, Patrick S.
ABSTRACT: 3D printing is a versatile fabrication method that offers the potential to realize complex 3D devices with metamaterial characteristics in a single process directly from a computer aided design. However, the range of functional devices that might be realized by 3D printing is limited by the current range of materials that are compatible with a given 3D printing process: fused deposition modelling (FDM), which is a widely used 3D printing method, typically employs only common thermoplastics. Here we describe the development of a magnetic feedstock based on polymer-ferrite composite that is compatible with FDM. The feasibility of the technique is demonstrated by the permittivity and permeability measurement of direct printed blocks and the fabrication of a complex 3D diamond-like lattice structure. The development of printable magnetic composites provides increased design freedom for direct realization of devices with graded electromagnetic properties operating at microwave frequencies.